Platelet status in cancer cachexia progression in ApcMin/+ mice - Cunningham, Patrice; Unger, Christian A.; Patton, Emma A.; Aiken, Akyla; Browne, Alea; James, Ella; Aladhami, Ahmed K.; Hope 3rd, Marion C.; VanderVeen, Brandon N.; Cardaci, Thomas D.; Murphy, E. Angela; Enos, Reilly T.; et al. (Frontiers in Immunology, 2023)
Cachexia, a complex wasting syndrome, significantly affects the quality of life and treatment options for cancer patients. Studies have reported a strong correlation between high platelet count and decreased survival in cachectic individuals. Therefore, this study aimed to investigate the immunopathogenesis of cancer cachexia using the ApcMin/+ mouse model of spontaneous colorectal cancer. The research focused on identifying cellular elements in the blood at different stages of cancer cachexia, assessing inflammatory markers and fibrogenic factors in the skeletal muscle, and studying the behavioral and metabolic phenotype of ApcMin/+ mice at the pre-cachectic and severely cachectic stages. Platelet measurements were also obtained from other animal models of cancer cachexia - Lewis Lung Carcinoma and Colon 26 adenocarcinoma. Our study revealed that platelet number is elevated prior to cachexia development in ApcMin/+ mice and can become activated during its progression. We also observed increased expression of TGFβ2, TGFβ3, and SMAD3 in the skeletal muscle of pre-cachectic ApcMin/+ mice. In severely cachectic mice, we observed an increase in Ly6g, CD206, and IL-10 mRNA. Meanwhile, IL-1β gene expression was elevated in the pre-cachectic stage. Our behavioral and metabolic phenotyping results indicate that pre-cachectic ApcMin/+ mice exhibit decreased physical activity. Additionally, we found an increase in anemia at pre-cachectic and severely cachectic stages. These findings highlight the altered platelet status during early and late stages of cachexia and provide a basis for further investigation of platelets in the field of cancer cachexia.